Ecological Basis of Grassland Conservation in india - DABADGHAO, P.M.; Patil, B D (Journal of Soil and Water Conservation, 2022)
Research work carried out in many parts of the world has convincingly proved the role of natural vegetation in the soil and water conservation. The soil and the vegetation growing on it, when left undisturbed, remain in equilibrium with each other at all stages of their development and together constitute a natural non-eroding system. The climax vegetation, may it be forest or grassland, protects the soil from the direct impact of rain water, prevents the surface water from gaining sufficient velocity to be dangerous, allows the absorption of water and replenishes the ground water supply which manifests itself in springs, wells and streams. The excess of water is harm- lessly carried through the great natural drainages back to the sea. The activities of man and his beast disturb this dynamic equillibrium and a series of damaging erosion consequences follow which at first less per- ceptible soon assume serious proportions. The soil is no longer effectively protected and is either washed down with accelerated sur- face runoff or blown away by wind, both processes resulting in damage to the valuable agricultural land. Consequences of these types are not unfamiliar in India. As in many other countries, soil conservation surveys carried out in India have attributed the main cause of erosion to the misuse of forests and grass- lands. The remedial measures obviously consist in the proper management of these national resources. Management of forests is generally based upon a careful blending of ecological and economic principles. The main emphasis is placed on planned utilization wherein only as much timber is cut as would be added per year in the form of growth thereby main- taining the essential structure of the forest more or less intact. Where this system is practised as in Government owned forests, the problem of erosion practically ceases to exist.